Superovulation with eCG alone or combined with the GnRH analogue buserelin improves transferable embryo production in weaned sows without affecting Day 6 embryo morphological, cellular, and transcriptomic parameters - Adelina Lopez-Jara; Manuela Garcia-Canovas; Henar Gonzalez-Ramiro; Carolina G. Cabrera-Gomez; David Gascon-Collado; Paula Blanco-Cueto; Maria A. Gil; Cristina Cuello; Inmaculada Parrilla; Emilio A. Martinez; Heriberto Rodriguez-Martinez; Cristina A. Martinez-Serrano (Animal Reproduction Science, 2026)

Deployment of a Dense Seismic Network on La Palma Island (2023-2024) for High-Resolution Imaging of the Velocity Structure Using Passive Seismic Methods - Javier Tortosa; Javier Almendros; Enrique Carmona; José Benito Martín; Janire Prudencio; Joan Antoni Parera-Portell; Rafael Abella; Carlos Araque-Pérez; José Morales; Pablo Rey-Devesa; Benjamin Heit; Xiaohui Yuan; et al. (Surveys in Geophysics, 2026)
We present the IMAGMASEIS project, a large-N seismic experiment carried out on La Palma (Canary Islands, Spain) between 2023 and 2024, aimed at high-resolution imaging of the crustal and upper mantle structure using passive seismic methods. The project involved the deployment of 235 temporary broadband and short-period seismic stations, supplementing 21 permanent stations, thus creating the densest seismic network ever installed on the island. The main goal is to characterise the magmatic plumbing system beneath Cumbre Vieja volcano, identify magma accumulation zones, and investigate structural changes related to the 2021 Tajogaite eruption. We describe the experimental design, network configuration, instrumentation, deployment strategies, and challenges encountered, including difficult terrain and logistical constraints. Preliminary results demonstrate the potential of the dataset for ambient noise tomography, receiver function analysis, and local earthquake studies. IMAGMASEIS provides a valuable resource for understanding volcanic and tectonic processes in oceanic island settings and serves as a model for cost-effective, high-density seismic deployments in similar environments.

Alarming conservation status of Western European steppe birds and their habitats: An expert-based review of current threats, traits and knowledge gaps - Julia Gómez-Catasús; Ana Benítez-López; Mario Díaz; David González del Portillo; Cristian Pérez-Granados; Juan Carlos Alonso; Beatriz Arroyo; Inmaculada Abril-Colón; Adrián Barrero; Rafael Barrientos; Luis Bolonio; Gerard Bota; et al. (Biological Conservation, 2025)

Gene dysregulation impairs placental angiogenesis in allogeneic pig pregnancies - Cristina A. Martinez-Serrano; Josep M. Cambra; Manuel Alvarez-Rodriguez; Inmaculada Parrilla; Cristina Cuello; Maria A. Gil; Emilio A. Martinez; Heriberto Rodriguez-Martinez (Animal Reproduction Science, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Plasma Levels of Neuron/Glia-Derived Apoptotic Bodies, an In Vivo Biomarker of Apoptosis, Predicts Infarct Growth and Functional Outcome in Patients with Ischemic Stroke - Inmaculada Díaz-Maroto; Beatriz Castro-Robles; Miguel Villar; Jorge García-García; Óscar Ayo-Martín; Gemma Serrano-Heras; Tomás Segura (Translational Stroke Research, 2025)
Evidence demonstrating the involvement of apoptosis in the death of the potentially salvageable area (penumbra zone) in patients during stroke remains limited. Our aim was to investigate whether apoptotic processes occur in penumbral brain tissue by analyzing circulating neuron- and glia-derived apoptotic bodies (CNS-ApBs), which are vesicles released into the bloodstream during the late stage of apoptosis. We have also assessed the clinical utility of plasma neuronal and glial apoptotic bodies in predicting early neurological evolution and functional outcome. The study included a total of 71 patients with acute hemispheric ischemic stroke (73 ± 10 years; 30 women). Blood samples were collected from these patients immediately upon arrival at the hospital (within 9 h) and at 24 and 72 h after symptom onset. Subsequently, isolation, quantification, and phenotypic characterization of CNS-ApBs during the first 72 h post-stroke were performed using centrifugation and flow cytometry techniques. We found a correlation between infarct growth and final infarct size with the amount of plasma CNS-ApBs detected in the first 72 h after stroke. In addition, patients with neurological worsening (progressive ischemic stroke) had higher plasma levels of CNS-ApBs at 24 h after symptom onset than those with a stable or improving course. Circulating CNS-ApB concentration was further associated with patients’ functional prognosis. In conclusion, apoptosis may play an important role in the growth of the cerebral infarct area and plasma CNS-ApB quantification could be used as a predictive marker of penumbra death, neurological deterioration, and functional outcome in patients with ischemic stroke.

Deciphering immune tolerance in allogeneic pig pregnancy - Josep M. Cambra; Cristina A. Martinez-Serrano; Heriberto Rodriguez-Martinez; Juan M. Vazquez; Cristina Cuello; Maria A. Gil; Emilio A. Martinez; Inmaculada Parrilla (Theriogenology, 2025)

Sustainable vine shoots-to-ethanol valorisation by a sequential acid/organosolv pretreatment - Diego Cardoza; María del Mar Contreras; Marta Lara-Serrano; Silvia Morales-delaRosa; Jose M. Campos-Martín; Inmaculada Romero; Eulogio Castro (Process Safety and Environmental Protection, 2024)

SDG monitoring framework for rural settlements mapping interactions with the Spanish Urban Agenda - Mónica Victoria Sánchez-Rivero; Inmaculada Bote Alonso; Mª Victoria Domínguez Serrano; Beatriz Montalbán Pozas (Sustainable Cities and Society, 2023)

Zr supported on non-acidic sepiolite for the efficient one-pot transformation of furfural into γ-valerolactone - Adrián García; Eleonora Monti; Alessia Ventimiglia; Nikolaos Dimitratos; Pablo J. Miguel; María Luisa López; Inmaculada Álvarez-Serrano; Tomás García; Maria Pilar Pico; Ana M. Dejoz; Benjamín Solsona (Biomass and Bioenergy, 2023)

GLAST versus GFAP as astroglial marker for the subcellular study of cannabinoid CB1 receptors in astrocytes - Svein Achicallende; Itziar Bonilla-Del Río; Maitane Serrano; Amaia Mimenza; Leire Lekunberri; Ilazki Anaut-Lusar; Nagore Puente; Inmaculada Gerrikagoitia; Pedro Grandes (Histochemistry and Cell Biology, 2022)

Neuronal and Glial Differentiation of Human Neural Stem Cells Is Regulated by Amyloid Precursor Protein (APP) Levels - Raquel Coronel; María Lachgar; Adela Bernabeu-Zornoza; Charlotte Palmer; Marta Domínguez-Alvaro; Ana Revilla; Inmaculada Ocaña; Andrés Fernández; Alberto Martínez-Serrano; Eva Cano; Isabel Liste (Molecular Neurobiology, 2019)

Buttermilk and Krill Oil Phospholipids Improve Hippocampal Insulin Resistance and Synaptic Signaling in Aged Rats - Joao Tomé-Carneiro; M. Carmen Crespo; Emma Burgos-Ramos; Cristina Tomas-Zapico; Alba García-Serrano; Pilar Castro-Gómez; Cesar Venero; Inmaculada Pereda-Pérez; Shishir Baliyan; Azucena Valencia; Javier Fontecha; Alberto Dávalos; et al. (Molecular Neurobiology, 2018)

Structural and functional analysis of the ovine laminin receptor gene (RPSA): Possible involvement of the LRP/LR protein in scrapie response - Ane Marcos-Carcavilla; Jorge H. Calvo; Carmen González; Carmen Serrano; Katayoun Moazami-Goudarzi; Pascal Laurent; Maud Bertaud; Hélène Hayes; Anne E. Beattie; Jaber Lyahyai; Inmaculada Martín-Burriel; Juan María Torres; et al. (Mammalian Genome, 2008)

IL-1 family members as candidate genes modulating scrapie susceptibility in sheep: localization, partial characterization, and expression - Ane Marcos-Carcavilla; Jorge H. Calvo; Carmen González; Katayoun Moazami-Goudarzi; Pascal Laurent; Maud Bertaud; Hélène Hayes; Anne E. Beattie; Carmen Serrano; Jaber Lyahyai; Inmaculada Martín-Burriel; Estefânia Alves; et al. (Mammalian Genome, 2007)